Growth and characterisation of pure B layers on Ge(hkl) and Si(hkl) utilizing molecular beam epitaxy - Schwarz, D.; Elsayed, A.; Gebert, L.; Schulze, J. (ECS Transactions, 2019)
Since the first investigations on pure B layers on Si have shown their potential application in high performance electronic devices, the interest in these structures increased rapidly. In this study, we report the growth of pure B layers on Ge(001), Si(001) and Si(111) substrates as well as on virtual Ge(100) substrates on Si utilizing molecular beam epitaxy in order to form ultra-shallow pn-junctions. A complementary metal oxide semiconductor compatible fabrication process was used afterwards to fabricate single mesa diodes. Further electrical characterizations of the devices show diode behavior with high ideality, low series resistance and low dark current density, compared to Schottky and homogenous doped, diodes. Concluding the given results, we discuss further research key aspects and possible applications of this novel material.
CRIS-Team Scopus Importer:2021-06-29